Social life contemporary social theory - Benzer, Matthias; Reed, Kate 1972- (Sage Publications, 2019)
In Social Life, the authors highlight, explain, and scrutinize socio-theoretical analyses of contemporary social relations and conditions - put forward by eight modern social theorists - and analyse how these have informed sociological inquiries into people's lives in today's social world. The book discusses the works of the following social theorists: Anthony Giddens, Pierre Bourdieu, Bruno Latour, Donna Haraway, Zygmunt Bauman, Jean-Francois Lyotard, Michel Foucault, Jean Baudrillard. In each chapter, the authors identify the key components of each theorist's conception of society and apply the theories outlined to specific, modern phenomena. This connection with modern-day phenomena allows for a critical interrogation of issues in contemporary society, including: Inequality and Capital, Power, Fear and Terrorism, Immune System Discourse, Suffering, and Climate Change. Essential reading for all sociology students studying social theory and the works of modern social theorists.